Importancia del mejoramiento genético en el cultivo caña de azúcar (Saccharum officinarum) - Macías Amador, Lisa Maoli (2024)
In the development of this case, the objective has been established to determine the importance of genetic improvement in sugarcane cultivation in order to increase production. In reference to the methods, the present research work, proposed as a practical component, has been developed through the exhaustive compilation of information, carrying out a thorough investigation in various publicly accessible web pages, scientific articles, degree theses, as well as sources and bibliographic documents available on various digital platforms. In results, the relevance of genetic improvement technologies in sugarcane cultivation is significantly manifested in the optimization of various key aspects for agricultural production, these technologies allow the genetic manipulation of sugarcane with the objective of improve specific characteristics such as yield, resistance to pests and diseases. In conclusion, the importance lies in the ability of genetic improvement to select and develop sugarcane varieties that exhibit desirable characteristics, such as greater resistance to pests and diseases, greater sucrose yield, and adaptation to specific growing conditions.